Pterygium surgery by means of conjunctival autograft: long term follow-up - Huerva,Valentín (2012)
PURPOSE: To demonstrate the long term of follow-up of the recurrence rate after conjunctival autograft for pterygium surgery. METHODS: A total of 112 patients operated for pterygium with conjunctival autografts and with more than one year follow-up were registered. Patients were called for voluntary examinations of their respective ocular surface statuses. Completing the study was only possible in 44 cases. Seven had bilateral pterygium. (N=51 operated pterygium). RESULTS: The mean follow-up time was 49.06 months. In 29.45% of the cases, attachment was performed using non-absorbable sutures (nylon 10/0), while fibrin glue was used in 70.55% of the cases. Six cases of recurrence (11.76%) were found. The recurrence rate between primary and recurrent pterygium, and between sutures and fibrin glue proved to be not statistically significant; p>0.05. There were no significant differences between women and men with respect to recurrence. The median of age in the recurrence group was 40 years old, in contrast to 55 in the non-recurrence group; p=0.01517. All of these recurrences were associated with patients of Hispanic origins (from Latin America); p=0.001506. CONCLUSIONS: After a long follow-up period after autograft pterygium surgery, there were no statistically significant differences in recurrence rates for the application of sutures as opposed to fibrin glue; similarly, there were no statistically significant differences between the use of autograft in primary and recurrent pterygium. The greatest risk factors for recurrence were young age and Hispanic ethnicity.